Dolotortula mniifolia (Sull.) Zand. (Pottiaceae, Musci) en Argentina - Suárez, Guillermo M.; Colotti, María T.; Schiavone, María M. (Lilloa, 2005)
Suárez, G. M., M. T. Colotti y M. M. Schiavone. 2005. Dolotortula mniifolia (Sull.) Zand. (Pottiaceae, Musci), en Argentina. Lilloa 42 (1-2). En esta nota se registra por primera vez al género y la especie para Argentina. Se presentan mapas de distribución.